Pengaruh Pengetahuan Pajak, Sanksi Pajak, dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak UMKM Dengan Sosialisasi Perpajakan Sebagai Variabel Moderasi - Dela Pusfitasari; Juli Ratnawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the impact of tax knowledge, tax sanctions, and taxpayer awareness on taxpayer compliance, and the position of tax socialization as a moderating variable for MSMEs selling in South Semarang District. This study uses quantitative techniques relying on primary data generated from the distribution of questionnaires to 100 MSMEs selected using purposive sampling techniques. Data management was carried out using Moderated Regression Analysis (MRA) using SPSS 25. The study states that tax knowledge, tax sanctions, and taxpayer awareness have a positive and significant impact on tax compliance, which means that the higher the understanding of MSMEs regarding tax provisions, the stricter the application of sanctions, and the greater awareness to fulfill tax obligations can increase compliance in calculating, paying, and reporting taxes. However, tax socialization has not been tested to strengthen the impact of tax knowledge, tax sanctions, and tax awareness on tax compliance of MSMEs. The results of this study indicate that increased compliance tends to be influenced by internal factors rather than the role of tax socialization implemented. Therefore, an interactive and sustainable tax socialization activity plan is needed to encourage tax compliance among MSMEs.